Problematika Perubahan Undang-Undang Tentang Mineral Dan Batu Bara: (Dikuasai Negara Tidak Sama Dengan Dimiliki Negara) - Tampubolon, Steven Paulus Hamonangan; Hartanto, Hartanto (Jurnal Hukum dan Sosial Politik, 2024)
Article 33 (3) of the 1945 Constitution of the Republic of Indonesia, is clear that the welfare of the people must be prioritized, however, the problem of mineral and coal mining, at the conceptual level, has not shown an impact on the welfare of the Indonesian people; The author appreciates this change in law. Currently, corruption related to mining has emerged again, namely a loss of IDR 271 trillion, which according to Bambang Hero S. is still an environmental loss or a loss to the country's economy. When compared to BLBI of 138 trillion and Asabri of around 22 trillion, this means that the trading system of tin as one of the mining commodities is the biggest corruption, which was unexpected by the public, but suddenly emerged after the election. Departing from the 1945 Constitution which uses the principle of managing oil and gas resources for the benefit of society and the state. So the problem formulation is how problematic occurs in changes to the regulations of Law no. 4 of 2009 until now it has become Law no. 3 of 2020. At the norm level, changes to the law have accommodated the principles of sustainability and legal certainty, even though implementing regulations do not yet exist. Returning to legal problems in Indonesia, problems often arise in the application of the law, not at the normative level.